PEMBERDAYAAN KADER KELUARGA SIAGA BANJIR DALAM MEMBANTU MENURUNKAN ANSIETAS DAMPAK BANJIR PESISIR SUNGAI DI KECAMATAN ASTAMBUL - Maria, Insana Maria; Filia Sofiani Ikasari; Faradilla Iedliany; Tassia Sekar Brilliant Santiago; Muhammad Nashih; Chrisnawati (STIKES Suaka Insan Banjarmasin, 2025)
Flood disasters have an impact not only materially and physically butpsychologically, namely anxiety, especially during repeated flood disasters. Theaim of this Community Service is to increase knowledge, skills and coordinationwith related parties in dealing with psychological problems of anxiety in floodproneresidents in the Astambul District area. The service method is carried outin three stages, namely preparation, implementation and evaluation. The resultsof Empowering Flood Alert Family Cadres in helping reduce anxiety about theimpact of flooding, the level of knowledge increased by 50%. Family cadres needto receive ongoing training in an effort to reduce anxiety about the impact offlooding so that the community gets maximum support from cadres.